On a nonlinear and chaotic non-ideal vibrating system with shape memory alloy (SMA) - Piccirillo, Vinicius [UNESP] (2008)
In this paper, we present nonlinear dynamic behaviour of a system which consists of a mass connected to a rigid support by a shape memory alloy (SMA) element and a damper. In order to disturb the system, a DC motor with limited power supply is connected to the mass, causing an interaction between the vibrating structure and the energy source. The SMA element is characterised using a one-dimensional phenomenological constitutive model, based on the classical Devonshire theory. We analyse the non-ideal system in form of two coupled nonlinear differential equations. Some interesting nonlinear phenomena as the Sommerfeld effect and nonlinear resonance including periodic, chaotic and hyperchaotic regime are presented.